Pengembangan TPQ Lansia Melalui Pelatihan Makharijul Huruf Dan Kajian Kitab Fiqih - Miftakhur Ridlo; Hari Prasetyo; Nining Khurrotul Aini; Imam Muzaqqi; Imelda Aulia; Istiqomah Imaniarti; Zujuk Khafidotul Umroh (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2023)
This article discusses the Qur'an source of Islam, holy book that contains the words of God. However, in reality, many Muslims are still unable to read the Qur'an properly and correctly, both children, adults and the elderly. Proficiency in reading Qur'an is one of the most important areas. The method used in service is Participaciory Action Research (PAR) Participatory activities in research that PAR is an action research activity as result of research process, namely research that begins with planning, carrying out actions or actions, and evaluating the results of actions. Counseling activities are carried out on Sunday, March 5, 2023 at 16.00 The material provided is law of tajweed, besides that elderly TPQ students get material about women's fiqh. Furthermore, lecturer provide tajweed material to students as reference for learning to read the Koran. The delivery of tajweed is a form of care to the elderly TPQ Pendowo hamlet. Besides that. The delivery of tajweed material is expected to help make it easier for students to understand the law of reading the Qur’an. Taman Pendidikan Al-qur'an is an institution that focuses on teaching reading and writing al-qur'an correctly in accordance with the law of tajweed. Al-Qur'an education park has the aim of forming a good person and holding fast to the Qur'an. The importance of the Qur'anic education park in human life is the reference of every problem. Therefore, every human being needs to instill a sense of love for the Qur'an.